Non-operative versus operative management of penetrating kidney injuries : a prospective audit - Moolman, Conray (Division of Urology, 2014)
To date there is little data on conservative management of penetrating renal trauma. The aim of this study was to review the management and outcome of a large patient cohort presenting with penetrating renal trauma to a tertiary referral centre in South Africa. All patients presenting with penetrating abdominal trauma and haematuria admitted to the Trauma Centre at Groote Schuur Hospital over a 19-month period was prospectively evaluated. Patients demographics, mechanism of injury, microscopic versus macroscopic haematuria, grade of injury, management decision (non-operative, laparotomy for other reasons without renal exploration or true renal surgery with Gerotas fascia opened), nonsurgical success rate, complications, hospital stay, transfusion requirements and nephrectomy rate were analysed.